High Migration and Invasion Ability of PGCCs and Their Daughter Cells Associated With the Nuclear Localization of S100A10 Modified by SUMOylation - Zhao, Qi; Zhang, Kexin; Li, Zugui; Zhang, Hao; Fu, Fangmei; Fu, Junjie; Zheng, Minying; Zhang, Shiwu (Frontiers in Cell and Developmental Biology, 2021)
Our previous studies have confirmed that cobalt chloride (CoCl2) or chemoradiotherapy could induce the formation of polyploid tumor giant cells (PGCCs). PGCCs are a special subpopulation of cancer cells that contribute to solid tumor heterogeneity. The size of PGCC was at least three times larger than regular diploid cancer cells. PGCCs have the properties of cancer stem cells (CSCs) and can express CSC markers CD44 and CD133. Daughter cells derived from PGCCs have strong proliferation, infiltration and migration abilities. However, the detailed molecular mechanism of daughter cells expressing mesenchymal phenotype and displaying strong abilities of proliferation and migration is unclear. As a plasminogen receptor, S100A10 which is closely associated with the invasion and metastasis of malignant tumors, was highly expressed in PGCCs with their daughter cells. In this study, CoCl2 was used to induce the formation of PGCCs in LoVo and HCT116 CRC cells. Cell functional experiments, co-immunoprecipitation, MG132 and ginkgolic acid treatment, western blot, and ChIP-Seq were used to identify the mechanism of S100A10 nuclear location. The proliferation and migration abilities of PGCCs and their daughter cells decreased significantly after S100A10 knockdown. In the control cells, S100A10 was mainly ubiquitinated, while in PGCCs and daughter cells, S100A10 was mainly SUMOylated, which was associated with S100A10 nuclear location. After SUMO1 was inhibited, the nuclear S100A10 in PGCCs and daughter cells decreased, and their proliferation and migration abilities significantly decreased. ChIP-Seq combined with real-time fluorescent quantitative PCR showed that S100A10 regulated the expression of neutrophil defensin 3 (DEFA3), receptor-type tyrosine-protein phosphatase N2 (PTPRN2), and rho guanine nucleotide exchange factor 18 (ARHGEF18), which were associated with actin dynamics and cytoskeleton remodeling. The expression of S100A10 in the nuclei and cytoplasm of rectal cancer after neoadjuvant chemoradiation (nCRT) and liver metastases increased compared with that in rectal cancer without nCRT. Taken together, the expression and nuclear localization of S100A10 modified by SUMOylation were associated with the high proliferation and migration of PGCCs and their daughter cells, and the differentiation, metastases, and relapse of CRCs by regulating the expression of ARHGEF18, PTPRN2, and DEFA3.